Optimization of a protocol for the evaluation of antibody responses to human papillomavirus (HPV) vaccination in low-resource settings - Emmanuel Timmy Donkoh; Edward Tieru Dassah; Ellis Owusu-Dabo (BMC, 2022)
Abstract Introduction Available human papillomavirus (HPV) vaccines could have an important primary role in cervical cancer prevention once their long-term immunogenicity and safety are evaluated at the population level. The aim of this study was to optimize an assay to be used in evaluating the long-term durability of HPV vaccine response following a pilot vaccination of adolescent girls in Ghana. Methods A rapid, high-throughput, indirect enzyme-linked immunosorbent assay (ELISA) was optimized for the detection and quantitation of anti-HPV L1 (late expression protein: types 6, 11, 16 and 18) immunoglobulin G (IgG) in human serum (n = 89). The utility of the assay was demonstrated using serum collected from a cohort of pre-adolescent girls (n = 49) previously vaccinated with a quadrivalent vaccine and non-immune serum obtained from age-matched controls (n = 40). Results The assay showed good discrimination of antibody levels between cases and control sera: seroprevalence of anti-HPV IgG antibodies was significantly higher among vaccinated than unvaccinated girls for both HPV-16 (63.3% vs. 12.5%; p < 0.001) and HPV-18 (34.7% vs. 20.0%; p = 0.042), respectively. Thirty-six months after receiving the third dose of vaccine, significantly higher mean anti-HPV-16 (0.618 vs. 0.145), anti-HPV-18 (0.323 vs. 0.309), and anti-HPV-6 (1.371 vs. 0.981) antibody levels were measured, compared to unvaccinated girls (all p < 0.05). A correlation between optical density and antibody activity indicated assay sensitivity to increasing levels of antibody activity. Conclusion We have successfully optimized and implemented a robust and sensitive assay for the evaluation of antibody responses among immunized adolescent girls for monitoring future large-scale HPV vaccination studies in low-income settings. Our results demonstrated greater immunoglobulin G antibody activity within serum drawn from adolescent girls immunized 36 months prior.